2017
DOI: 10.1186/s13102-017-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recovery strategies upon performance and perceptions following fatiguing exercise: a randomized controlled trial

Abstract: BackgroundDespite debate regarding their effectiveness, many different post-exercise recovery strategies are used by athletes. This study compared five post-exercise recovery strategies (cold water immersion, contrast water immersion, active recovery, a combined cold water immersion and active recovery and a control condition) to determine which is most effective for subsequent short-term performance and perceived recovery.MethodsThirty-four recreationally active males undertook a simulated team-game fatiguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
(74 reference statements)
0
21
0
Order By: Relevance
“…In the current review, we have therefore only included studies that have compared an active cool-down with a passive cool-down that consists of sitting, lying, or standing (without walking). Active cool-downs that combine exercise with cold water immersion [ 25 ] are also excluded. We have also restricted the review to studies that have investigated the effects of performing an active cool-down within approximately 1 h after exercise, because findings from a recent survey suggest that this most closely replicates the cool-down procedure of many recreational and professional athletes [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current review, we have therefore only included studies that have compared an active cool-down with a passive cool-down that consists of sitting, lying, or standing (without walking). Active cool-downs that combine exercise with cold water immersion [ 25 ] are also excluded. We have also restricted the review to studies that have investigated the effects of performing an active cool-down within approximately 1 h after exercise, because findings from a recent survey suggest that this most closely replicates the cool-down procedure of many recreational and professional athletes [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conflicting findings have been reported with regard to the effects of an active cool-down on next-day(s) performance, with some studies reporting small to moderate magnitude benefits of an active cool-down compared with a passive cool-down, and others reporting trivial effects or small decreases (Table 2 ) [ 25 , 30 , 39 – 49 ]. Most studies, however, report trivial effects, with some studies reporting beneficial effects and only a few studies reporting harmful effects.…”
Section: Effects On Sports Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have confirmed the positive effects of physical activities on different populations [10]. These effects include reduced cardiovascular disease, reduced mortality rates, improvement in and control of blood pressure, controlled blood glucose, increased sense of wellbeing, and improvement in physical performance [9,11,12].…”
Section: Introductionmentioning
confidence: 99%